2017
DOI: 10.4049/jimmunol.1600731
|View full text |Cite
|
Sign up to set email alerts
|

CD63-Mediated Antigen Delivery into Extracellular Vesicles via DNA Vaccination Results in Robust CD8+ T Cell Responses

Abstract: DNA vaccines are attractive immunogens for priming humoral and cellular immune responses to the encoded Ag. However, their ability to induce Ag-specific CD8 T cell responses requires improvement. Among the strategies for improving DNA vaccine immunogenicity are booster vaccinations, alternate vaccine formulations, electroporation, and genetic adjuvants, but few, such as extracellular vesicles (EVs), target natural Ag delivery systems. By focusing on CD63, a tetraspanin protein expressed on various cellular mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 58 publications
3
33
2
Order By: Relevance
“…Exosomes with surface-displayed antigens can also be used as anticancer vaccines. In one study, fusion of ovalbumin (OVA) antigen to CD63 produced OVA exosomes that improved the immunogenicity of DNA vaccines and prevented tumor growth in a xenograft model 64 . Membrane-bound antigen cargo can also be displayed by the C1C2 domain of lactadherin, which binds and localizes to phosphatidylserine-containing exosome membranes, to increase levels of cytokines that support immunogenicity.…”
Section: Surface Engineeringmentioning
confidence: 99%
“…Exosomes with surface-displayed antigens can also be used as anticancer vaccines. In one study, fusion of ovalbumin (OVA) antigen to CD63 produced OVA exosomes that improved the immunogenicity of DNA vaccines and prevented tumor growth in a xenograft model 64 . Membrane-bound antigen cargo can also be displayed by the C1C2 domain of lactadherin, which binds and localizes to phosphatidylserine-containing exosome membranes, to increase levels of cytokines that support immunogenicity.…”
Section: Surface Engineeringmentioning
confidence: 99%
“…Antigen-presenting EXOs from B lymphocytes and DCs containing major histocompatibility complex I/II (MHCI/II) complexes could stimulate CD4 + and CD8 + T cells as therapeutic HPV vaccines [182]. Kanuma et al also demonstrated that CD63-mediated antigen delivery into EVs via DNA vaccination leads to strong CD8 T cell responses [183]. Therefore, the experimental validation studies described above indicate that EXOs hold promise as nano delivery vehicles for cancer treatment.…”
Section: Application Of Evs In Therapeutic Strategiesmentioning
confidence: 99%
“…Since the EV membrane is enriched with membrane proteins that associate with lipid rafts, any transmembrane protein on the surface of an EV can theoretically be used as a fusion partner. In order to deliver protein cargoes, researchers have fused cargo proteins with membrane proteins of EVs, such as tetraspanin and lactadherin [68–70]. Exosomal membrane proteins were also successfully fused with luciferase and fluorescent proteins to enable the tracking of exosomes in animal models and allow their fates to be monitored [68,71,72].…”
Section: Advantages Of Evs Over Other Nanoparticles From the View Of mentioning
confidence: 99%